A survey of Canadian renal transplant surgeons: Use of ureteric stents and technique of the ureteroneocystotomy - Reynolds, Luke F.; Kroczak, Tad; Honey, R. John; Pace, Kenneth T.; Lee, Jason Y.; Ordon, Michael (Canadian Urological Association Journal, 2018)
Introduction: The role of ureteric stenting in renal transplant has been well-demonstrated. The goal of this survey was to determine the use of ureteric stents by Canadian transplant surgeons and how the ureteroneocystotomy and followup is performed. Methods: An online survey was sent to the 40 surgeon members of the Canadian Society of Transplantation. The primary outcome was the rate of ureteric stent use at the time of renal transplantation. The secondary outcomes were the ureteric stent dwell time, use and type of prophylactic antibiotics, and the use of routine post-transplant ultrasonography. Results: All respondents (25) used ureteric stent routinely and 92% remove the stent between four and six weeks postoperatively. Prophylactic antibiotics were used 64% of the time for ureteric stent removal. The majority of surgeons do not routinely perform a post-stent removal ultrasound. Fifty-six percent of respondents perform a refluxing anastomosis. Conclusions: Ureteric stents are routinely used in renal transplant in Canada. Areas for improvement and topics of debate identified from this survey are the need for peri-stent removal antibiotics, the role of post-stent removal ultrasound, the duration of stent dwell time, and the need for a non-refluxing ureteroneocystotomy.